STRATEGI PENGELOLAAN AKUN YOUTUBE HOTMAN PARIS SHOW - Rahmadina Rahmadina (Jurnal Visi Komunikasi, 2022)
This study was introduced by the appearance of technology in the digital era. Youtube is the social media that often used by society today.This study is using the concept of new media, Youtube, management, and management function of POAC (Planning, Organizing, Actuating, Controlling). This study also explaining how the management strategy of Hotman Pari Show youtube account. The methods used in this study is descriptive qualitative with the qualitative approach to describe the result of the study by concluding the interview's result (indepth interview). With three key informant of Hotman Paris Show which are the head of social media officer, the staff of social media officer, and the producer.The result of this study concluded how the management strategy of Hotman Paris Show youtube account in gaining their objective, which is to maximizing every show by creating the headline, caption, and thumbnail as good as possible, so it would make the good impression for the audience when they saw it. Moreover, the production team of Hotman Paris Show has implementing the strategy to always create the theme of the event that inspiring people and became the trending topic of the society. The production team and the social media team have the important role in the implementation of Hotman Paris youtube account because their completing one and another